ANALISIS KINERJA KEUANGAN PADA PT BAYAN RESOURCE Tbk Per 2015-2017 - Muhammad Maulana (LPPM University 17 Agustus 1945 Samarinda, 2018)
Company performance is an illustration of the financial condition of a company by conducting a financial analysis, so that it can be known about the good and bad financial condition of a company that reflects work performance in a certain period. To find out how good a company's financial performance is, it is necessary to conduct an assessment and performance measurement. One assessment and measurement of performance can be reflected through an analysis of financial ratios.This research was conducted to find out how well the financial performance performed by PT Bayan resources a coal mining company in the 2015-2017 period by analyzing the ratio of: (1) profitability ratios (2) solvency ratios, (3) liquidity ratios , (4) activity ratio. The hypothesis of this research is based on the phenomenon, which is based on the market value of coal which has decreased over the period of 2015-2017.Based on the results of the study, the hypothesis for calculating profitability ratios, activity ratios and solvency ratios is proven to be acceptable, while the hypothesis for liquidity ratios is not proven, namely rejected, meaning that fluctuations in coal price increases can result in the use of corporate liquidity to pay company bills so that the level of liquidity of the company can be reduced